Cell Cycle Entry Control in Naïve and Memory CD8+ T Cells - Lewis, David A.; Ly, Tony (Frontiers in Cell and Developmental Biology, 2021)
CD8+ T cells play important roles in immunity and the growing field of immuno-oncology. Upon antigen recognition and co-stimulation, naïve CD8+ T cells escape from dormancy to engage in a complex programme of cellular growth, cell cycle entry and differentiation, resulting in rapid proliferation cycles that has the net effect of producing clonally expanded, antigen-specific cytotoxic T lymphocytes (CTLs). A fraction of activated T cells will re-enter dormancy by differentiating into memory T cells, which have essential roles in adaptive immunity. In this review, we discuss the current understanding of cell cycle entry control in CD8+ T cells and crosstalk between these mechanisms and pathways regulating immunological phenotypes.